Digital Leadership of School Principals in Enhancing Technology-Based Learning Quality - Irmawati Thahir (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research examines the role of school principals' digital leadership in enhancing technology-based learning quality in elementary schools during the Society 5.0 era. The Society 5.0 era demands educational transformation that integrates digital technology with humanistic approaches to create quality learning. School principals, as educational leaders, have a strategic role in directing digital transformation in schools. This research employs a qualitative approach with a case study method in several elementary schools that have implemented technology-based learning. Research findings indicate that principals' digital leadership encompasses five main dimensions: clear digital vision, technology competence, teacher capacity development, change management, and innovation culture building. These findings provide theoretical contributions to educational leadership concept development in the digital era and practical implications for principals' professional development.